Family based and case–control designs reveal an association of TFAP2A in nonsyndromic cleft lip only among Vietnamese population - Duc Minh Nguyen; Satoshi Suzuki; Hideto Imura; Teruyuki Niimi; Hiroo Furukawa; Thanh‐Van Ta; Son Minh Tong; Tra Thu Nguyen; Loc Nguyen Gia Pham; Duy Le Tran; Nagato Natsume (Molecular Genetics & Genomic Medicine, 2021)
Abstract Aims Dozens of causative genes and their mechanisms of nonsyndromic cleft lip with or without cleft palate (NSCL/P) were revealed through genome‐wide association and linkage studies. Results were, however, not always replicated in different populations or methodologies. This study used case–control and family based approaches to investigate the etiology of NSCL/P and its two subtypes: nonsyndromic cleft lip only (NSCLO) and nonsyndromic cleft lip and palate (NSCLP) among the Vietnamese population. Methods Two hundred and seventeen NSCL/P case‐parent trios (one affected child and two parents), including 105 NSCLO and 112 NSCLP were involved for a family based design; and 273 ethnic and region‐matched healthy controls with no cleft history in their families were recruited for a case–control design. Three SNPs consisting of TFAP2A (rs1675414 and rs303048) and 8q24 (rs987525) were genotyped using the TaqMan SNP genotyping assay. Results TFAP2A rs1675414 was associated with NSCLO, replicated by both case‐control and family based tests. Other SNPs yielded no evidence of susceptibility to NSCL/P or two subtypes. Conclusion The current investigation suggests an intriguing role of TFAP2A in the etiology of NSCLO among the Vietnamese population.